Predictive Mortality Factors after Decompressive Craniectomy in Ischemic Stroke - Leite, Maria Luísa Brito Almino; Leite, Matheus Silva; Barbosa, Fernando Diogo; Kessler, Iruena Moraes (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Background Decompressive craniectomy is a consolidated method for the treatment of malignant ischemic stroke (iS) in the territory of the middle cerebral artery. Thus, factors contributing to mortality constitute an important area of investigation.Objective To evaluate the epidemiological clinical profile and predictors of mortality in a single-center population of patients undergoing decompressive craniectomy for the treatment of malignant iS.Methods A single-center retrospective study was performed in 87 patients with malignant iS subjected to emergency decompressive craniectomy from January 2014 to December 2017. Age, gender, laterality, aphasia, time interval between disease onset and treatment, and clinical and neurological outcomes using the Glasgow coma scale were assessed. The patients were stratified by age: a group of participants 60 years old or younger, and a group of participants older than 60 years old for assessment of survival and mortality by the Kaplan-Meier test and log-rank comparison. The intensity of the association between demographic and clinical variables was evaluated by multivariate Cox regression.Results Ischemic stroke was prevalent in patients with hypertension (63.29%). Seventy-seven (84%) patients had some type of postoperative complication, mostly pneumonia (42.8%). The risk of death was 2.71 (p = 0.0041) and 1.93 (p = 0.0411) times higher in patients older than 60 and with less than 8 points on the Glasgow coma scale, respectively.Conclusion Malignant iS has a significant mortality rate. Age above 60 years and Glasgow coma scale values below 8 were statistically correlated with unfavorable prognosis.
Keywords: ischemic stroke; cerebrovascular stroke; middle cerebral artery; decompressive craniectomy